PR practitioners’ use of social media: validation of an online relationship management model applying structural equation modeling - El-Kasim, Mukhtar; Syed Arabi Idid, (Penerbit Universiti Kebangsaan Malaysia, 2017)
The emergence of social media had shaped the relationships between public relations practitioners, organizations and publics. Social media provides numerous opportunities of maintaining mutual relationships between these entities, specifically because of its speed and interactive potentials. Hence, many organizations established social media sites and public relations practitioners utilized it in their workplace. However, most of the studies that examined the influence of social media in shaping organizations-public relationships were not carried out on a theoretical continuum. Hence, little is known on the influence of social media on public relations practice from developing countries’ perspective. The motivation of this study was to propose and validate a model which explains how public relations practitioners use social media for enhancing mutual relationships with their strategic publics. The significance of conducting this study is to bring to light the influence of social media in public relations practice from a country that has different demographic, economic and political settings from countries which most of the studies of this nature were carried out before. Technology Acceptance Model (TAM) was utilized as the theoretical guide of this study. Thus, the actual use of social media among PR practitioners was measured by a construct named, Perceived Mutual Relationship. Perceived Mutual Relationship was also measured from three dimensions which included: trust; commitment and satisfaction. Data were collected from 513 public relations practitioners in Nigeria through a systematic random sampling. Structural Equation Modeling (SEM) was employed for analysis of the model. The study used TAM to explain reasons why practitioners utilized social media for enhancing mutual relationships with their publics. Specifically, the validated model proved that use of social media for relationship management was explained by 73%. The validated model provides public relations researchers with a theoretical framework to investigate how social media could be utilized in promoting mutual relationships between public relations practitioners, their organizations and target publics.